Land use and land cover change impacts on the regional climate of non-Amazonian South America: A review - Salazar, Alvaro (2015)
Land use and land cover change (LUCC) affects regional climate through modifications in the water balance and energy budget. These impacts are frequently expressed by: changes in the amount and frequency of precipitation and alteration of surface temperatures. In South America, most of the studies of the effects of LUCC on the local and regional climate have focused on the Amazon region (54 studies), whereas LUCC within non-Amazonian regions have been largely undermined regardless their potential importance in regulating the regional climate (19 studies). We estimated that 3.6million km^2 of the original natural vegetation cover in non-Amazonian South America were converted into other types of land use, which is about 4 times greater than the historical Amazon deforestation. Moreover, there is evidence showing that LUCC within such fairly neglected ecosystems cause significant reductions in precipitation and increases in surface temperatures, with occasional impacts affecting neighboring or remote areas. We explore the implications of these findings in the context of water security, climatic extremes and future research priorities.